Control of Lysis of T4-infected Escherichia coli - Couse, Nancy L. (1968)
The lysis of Escherichia coli B/5 infected with T4Dr48 could be delayed by addition of 9-aminoacridine (9AA). Infected cells showed an early period of maximal response followed by a decline in sensitivity. The ultimate rate of lysis was also affected by the dye. Deoxyribonucleic acid (DNA), protein, and lysozyme synthesis began at the normal time in complexes inhibited by 9AA addition. The rates of synthesis of these macromolecules were lower in the presence of the dye, with DNA and lysozyme synthesis being more strongly affected than total protein synthesis. Penicillin-sensitive cell wall synthesis stopped at about 10 min after infection. Inhibition of oxidative metabolism by early potassium cyanide addition prevented lysis in the presence of intracellular lysozyme. The cyanide-sensitive event occurred at about 20 min in normal infections, and between 30 and 40 min in 9AA-inhibited infections. 9AA could alter both the time at which the cyanide-sensitive event occurred and the time of lysis. Addition of chloramphenicol did not prevent lysis once intracellular lysozyme was present. Lysis from without of infected cells consisted of three phases: an initial sensitivity, followed by a short period of resistance, and then a return to sensitivity in normal infections. The demonstration of the late return to sensitivity depended on the presence of intracellular lysozyme, and could be delayed by 9AA addition.